1999
DOI: 10.1523/jneurosci.19-13-05228.1999
|View full text |Cite
|
Sign up to set email alerts
|

Selective Excitation of Subtypes of Neocortical Interneurons by Nicotinic Receptors

Abstract: The cellular mechanisms by which neuronal nicotinic cholinergic receptors influence many aspects of physiology and pathology in the neocortex remain primarily unknown. Whole-cell recordings and single-cell reverse transcription (RT)-PCR were combined to analyze the effect of nicotinic receptor agonists on different types of neurons in acute slices of rat neocortex. Nicotinic receptor agonists had no effect on pyramidal neurons and on most types of interneurons, including parvalbuminexpressing fast spiking inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
205
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(227 citation statements)
references
References 62 publications
(91 reference statements)
18
205
1
1
Order By: Relevance
“…One clue from our data was that ␣4* nAChRs were highly expressed on GABAergic cortical interneurons and their relative levels of expression on these neurons increased following whisker trimming. This finding is consistent with previous work showing that mRNA for ␣4* nAChR are present in GABAergic cortical neurons (Porter et al, 1999;Couey et al, 2007). Furthermore, we show that activating ␣4* nAChRs in vivo by bath application or direct micro-injection of ␣4* nAChR agonist into layer 4 depressed whisker-evoked responses by 30 -50% in control mice, similar to that seen after 3-7 d of whisker deprivation.…”
Section: Mechanisms Of Experience-based Cortical Depressionsupporting
confidence: 93%
See 1 more Smart Citation
“…One clue from our data was that ␣4* nAChRs were highly expressed on GABAergic cortical interneurons and their relative levels of expression on these neurons increased following whisker trimming. This finding is consistent with previous work showing that mRNA for ␣4* nAChR are present in GABAergic cortical neurons (Porter et al, 1999;Couey et al, 2007). Furthermore, we show that activating ␣4* nAChRs in vivo by bath application or direct micro-injection of ␣4* nAChR agonist into layer 4 depressed whisker-evoked responses by 30 -50% in control mice, similar to that seen after 3-7 d of whisker deprivation.…”
Section: Mechanisms Of Experience-based Cortical Depressionsupporting
confidence: 93%
“…Furthermore, we show that activating ␣4* nAChRs in vivo by bath application or direct micro-injection of ␣4* nAChR agonist into layer 4 depressed whisker-evoked responses by 30 -50% in control mice, similar to that seen after 3-7 d of whisker deprivation. Indeed, several electrophysiological studies using both human and rodent cortical tissue have shown that ␣4* nAChR activation rapidly depolarizes cortical interneurons, that can be blocked by the ␣4* nAChR antagonist DH␤E (Xiang et al, 1998;Porter et al, 1999;Alkondon et al, 2000;Christophe et al, 2002;Klaassen et al, 2006;Couey et al, 2007;Mann and Mody, 2008). Therefore one possible mechanism underlying the depression of whisker-evoked responses is that ␣4* nAChRs may be enhancing GABAergic inhibition in deprived barrel columns.…”
Section: Mechanisms Of Experience-based Cortical Depressionmentioning
confidence: 99%
“…Based on combined electrophysiological (15) and molecular studies (16), the observed increase in inhibitory I mean is very likely a result of an enhanced nicotine-evoked GABA release from Chrna4 S252F/wt or Chrna4 ϩL264/wt -expressing cortical interneurons that form synapses on the somata, axon initial segments, or dendrites of pyramidal cells. To determine whether nicotine acts on ␣4-subunit-containing nAChRs located on GABAergic interneuron terminals, we measured its effect on miniature IPSCs (mIPSCs) recorded in the absence of presynaptic Ca 2ϩ entry by blocking action potentials with tetrodotoxin (TTX) and voltage-gated Ca 2ϩ channels with cadmium.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas rodent cortical layer II͞III and V pyramidal neurons are not directly depolarized by nicotinic cholinergic agonists (16,18,19), selected subtypes of cortical interneurons express functional nAChRs assembled from ␣4 and ␤2 subunits (with or without ␣5) or ␣7 subunits (16,20). Inhibitory interneurons release GABA and have been implicated in nicotine-induced hippocampal seizures (21), as well as in models of cortical or hippocampal pathophysiology that result from nAChR activation, modulation of GABAergic tone, and subsequent inhibition or disinhibition of neuronal networks (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation